Observation and evaluation of surface and underground space changes in well salt mining based on InSAR: a case study of Qingjiang salt mine, Zhangshu, China - Hua Gao; Xiaoliang Luo; Hui Lin; Guangcai Feng; Lvchun Wang (International Journal of Digital Earth)
Deep well salt extraction not only readily leads to the salinization of the surrounding terrain but may also cause regional subsidence, posing significant risks to both infrastructure and local populations. Understanding the quantitative relationship between changes in underground space and surface deformation is essential for balancing salt production and safety concerns. In this study, we used Sentinel-1 data from January 2018 to January 2022 and SBAS InSAR to quantify ground deformation within the salt mine region of Zhangshu. Our results indicate that the deformation area spans over 1.5 km², with the highest deformation rate of 38.5 mm/yr. Some areas show increase in the deformation rate. Employing the Mogi model, we conducted an inversion analysis to estimate the subsurface material loss rate. The net annual loss rate of the region is 8.65×104 m3/yr. Based on cumulative volume changes, the potential max earthquake magnitude is estimated at Mw 5.11, with a possibility of reaching Mw 5.5 in 60 years without intervention. To mitigate geological disaster risks, we recommend implementing building height restrictions, comprehensive infrastructure monitoring, careful mining and backfilling strategies.